2012
DOI: 10.4102/curationis.v35i1.64
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of mother to child transmission lay counsellors: Are they adequately trained?

Abstract: South Africa's high prevalence of human immunodeficiency virus (HIV) infected women requires a comprehensive health care approach to pregnancy because of the added risk of their HIV status. As a result of the shortage of health care workers in South Africa, lay counsellors play important roles in the prevention of mother to child transmission of HIV (PMTCT). There is no standardization of training of lay counsellors in South Africa, and training varies in length depending on the training organisation. The stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Similar studies in this area indicated that many counsellors were found to be untrained [ 11 , 16 ]. Studies have indicated that training varies in length and content, depending on the training organisation [ 17 ], as was the case in this study, as they received training from different HCT organisations. Although not ascertained in this study, there could also be variation of training among lay counsellors in the same health facility.…”
Section: Discussionmentioning
confidence: 99%
“…Similar studies in this area indicated that many counsellors were found to be untrained [ 11 , 16 ]. Studies have indicated that training varies in length and content, depending on the training organisation [ 17 ], as was the case in this study, as they received training from different HCT organisations. Although not ascertained in this study, there could also be variation of training among lay counsellors in the same health facility.…”
Section: Discussionmentioning
confidence: 99%
“…Lay counselling represents one such service. Lay counsellors in South Africa are non-professional service providers and typically have no formal qualifications or professional certificates and are not affiliated with a professional regulatory body (Thurling & Harris, 2012). They provide social and emotional support and are most active in the provision of trauma counselling, education related to the prevention of gender-based violence, pre- and post-test HIV counselling, and counselling services related to promoting medication adherence for chronic medical health problems (Jansen van Rensburg, 2008; Peltzer, 2012).…”
mentioning
confidence: 99%
“…Non-parametric tests were used to compare the scores Research on HCT mostly focuses on the implementation challenges (Friedman et al, 2007) and effectiveness of services (Myint & Mash, 2008; and the experiences of HCT counsellors (Mavhandu-Mudzusi et al, 2007;Richards and Marquez, 2005;Rohleder & Swartz, 2005). The governance, remuneration, lack of training and supervision and management of lay counsellors were identified as crucial challenges in implementation (Daniels et al, 2010;Friedman, 2005;Peltzer & Davids, 2011;Schneider et al, 2008;Thurling & Harris, 2012). A few studies evaluated the ability of lay counsellors to implement counselling.…”
Section: Discussionmentioning
confidence: 99%